Uv curable and long lasting antimicrobial paint coating - AKSU, MEHMET BURAK (My University, 2023)
The harmful effects of microorganisms seriously threaten human health and life. Since prehistoric times, many diseases are caused by microorganisms and such types of diseases are still increasing. Antimicrobial resistance is the one of the main concern about the fight against to bacteria. Biocidal products show chemical and biological effects against harmful microorganisms, preventing their growth and biofilm formation. There are many biocidal compounds used against to bacteria. One of them is the cationic polymer that possess hydrophobicity and polar groups (cationic charge) to mimic the host defense peptides’ structure. Polymeric antibacterial agents represent new developing direction in this field and offer great promise for enhancing activity. Here, we synthesized UV curable quaternary monomers/oligomers possessing alkyl functionality. After addition into the UV varnish formulation, coated surfaces showed the 100% killing and repeated cycle efficiency against to E.coli and S.aureus.
Keywords: Kimya Mühendisliği ve Teknolojisi; Biyoteknoloji; Diğer; Kimyasal Teknolojiler; Polimer Teknolojisi; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Biotechnology; Other; Chemical Technologies; Polymer Technology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, KİMYASAL; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, CHEMICAL; Akışkan Akışı ve Transfer İşlemleri; Kolloid ve Yüzey Kimyası; Kimyasal Sağlık ve Güvenlik; Kataliz; Kimya Mühendisliği (çeşitli); Genel Kimya Mühendisliği; Fizik Bilimleri; Fluid Flow and Transfer Processes; Colloid and Surface Chemistry; Chemical Health and Safety; Catalysis; Chemical Engineering (miscellaneous); General Chemical Engineering; Physical Sciences